Danças de nós: da dança do ventre à dança tribal: entre pistas e reflexões de uma arte cênica em fluxo - Ana Clara Santos Oliveira (2023)
The fusion belly dance, generically treated as tribal dance, suggests the transformation of concepts, techniques and aesthetic elements of different social groups in an updated dimension. From the remarkable effervescence of oriental dance, in this situation, belly dancing, is characterized by the cultivation of “ethnic” plurality that, fond of reprocessing and mutations, conditions a field of tangible problems in the current world. Like every branch on the rise and filled with a nature of innovation, there is a need to map numerous themes in the development of the field. The general objective of this research is to understand the state of the art of fusion belly dancing in Brazil, presenting a survey of its artistic and pedagogical information together with cultural, economic, social and political issues. To account for this design, this study was based on the mixed method that provides for the quantitative and qualitative triangulation of data. The methodological approach combines a literature review, field research via the application of questionnaires and semi-structured interviews with people who practice fusion belly dancing in Brazil and, finally, reflection according to the following categories: dimensions of pedagogical aspects, dimensions of creative aspects, dimensions economic and politicalsocial aspects. The results support the importance of recognizing the narratives of dance practitioners for the “pluriversal” understanding of the scene. It is hoped that this research can provoke "movements" in the field both in subsidizing future research and in the sense of inspiring debates on educational, artistic, professional instrumentalization, sectorial dance policies, and not least, themes that can encourage humanization processes.